Water isotopes from Lake Tininnilik region, West Greenland, July 2022 ... - B. Das, Sarah (NSF Arctic Data Center, 2024)
Lake Tinninilik is an ice-marginal lake in western Greenland. It is dammed by Sarqardliup Glacier to the East and North, and drains on a quasi-decadal timescale when lake volume reaches a critical threshold. When Lake Tininnilik does drain, it discharges ~2 cubic kilometers (km3) of lake water in Sarqardleq Fjord to the North. Water samples were collected in July 2022 from streams around the lake and surface and depth water samples from the lake itself during a periodic low-stand. Paired d18O and dD analyses are provided here and are used in this study to understand end-member water source fractions in the lake as well as insight into lake mixing. Complementary data (trace metal (ICP-MS), ion (ion chromatography), and nutrient (colorimetric nutrient analysis) geochemical data) are reported elsewhere (doi:10.18739/A2F47GW34). The aim of the project is to understand whether Greenland ice-marginal lakes are an important source of nutrients to coastal waters into which they drain. ...